Praktik Keagamaan pada Penderita HIV/AIDS - Muhammad Bagus Andrianto (Jurnal Kesmas Asclepius, 2021)
This study aims to determine the relationship between religious practices of people living with HIV/AIDS. The design in this study is a descriptive analytic study. The results of the study from 153 respondents that most of the religious practices of Islam in the HIV/AIDS group were moderate 105 (68.6%). There is a significant relationship between religious practices in people with HIV/AIDS. Most of the religious practices are moderate and most are moderate. In conclusion, there is a significant relationship between the level of religious practice of people living with HIV/AIDS. Keywords: HIV/AIDS, Religious Practice